Both temperature fluctuations and East Asian monsoons have driven plant diversification in the karst ecosystems from southern China. Issue 22 (25th October 2017) - Kong, Hanghui; Condamine, Fabien L.; Harris, AJ; Chen, Junlin; Pan, Bo; Möller, Michael; Hoang, Van Sam; Kang, Ming
Abstract: Karst ecosystems in southern China are species‐rich and have high levels of endemism, yet little is known regarding the evolutionary processes responsible for the origin and diversification of karst biodiversity. The genus Primulina (Gesneriaceae) comprises ca. 170 species endemic to southern China with high levels of ecological (edaphic) specialization, providing an exceptional model to study the plant diversification in karsts. We used molecular data from nine chloroplast and 11 nuclear regions and macroevolutionary analyses to assess the origin and cause of species diversification due to palaeoenvironmental changes and edaphic specialization in Primulina . We found that speciation was positively associated with changes in past temperatures and East Asian monsoons through the evolutionary history of Primulina . Climatic change around the mid‐Miocene triggered an early burst followed by a slowdown of diversification rate towards the present with the climate cooling. We detected different speciation rates among edaphic types, and transitions among soil types were infrequently and did not impact the overall speciation rate. Our findings suggest that both global temperature changes and East Asian monsoons have played crucial roles in floristic diversification within the karst ecosystems in southern China, such that speciation was higher when climate was warmer and wetter. This is the first study to directly demonstrate that past monsoon activity is positively correlated with speciation rate in East Asia. This case study could motivate further investigations to assess the impacts of past environmental changes on the origin and diversification of biodiversity in global karst ecosystems, most of which are under threat.